Unrecognized biodiversity in a world's hotspot: Three new species of Melanorivulus (Cyprinodontiformes: Rivulidae) from tributaries of the right bank of the Rio Paraná basin, Brazilian Cerrado - Volcan, Matheus V.; Severo-Neto, Francisco [UNESP]; Lanés, Luis Esteban K. (Pensoft Publishers, 2018)
The genus Melanorivulus presents a wide geographical distribution in the Neotropical region. Among Melanorivulus, the M. pictus species group has currently 18 species distributed in the Brazilian Cerrado, mainly in the upper Rio Paraná basin, with some species occurrences in the upper Rio Araguaia and Tocantins. In the present study, we describe three new Melanorivulus species, belonging to the M. pictus species group from different drainages of the right bank of the Rio Paraná basin in Mato Grosso do Sul state, Brazil. These new species are easily distinguished from the others by their unique colour patterns. Melanorivulus interruptus is distinguished from all species of the M. pictus group by the presence of oblique chevron-like red bars interrupted, mainly on the midline of the flank in males; while M. ivinhemensis by the yellow colouration of the caudal fin with thin red bars arranged only in the median region of the fin in males. Melanorivulus amambaiensis is distinguished from all species of the M. pictus species group by having an orange anal fin or sometimes more reddish-orange with distal margin grey or dark grey and chevron-like bars along the body, distinctly branched ventrally forming an inverted Y-shape in males. The high diversity of the Melanorivulus species with high levels of endemism demands the development of conservation strategies to avoid the loss of their vulnerable habitats in the Cerrado biome. We expect presence of more species of the M. pictus species group also along the lower reaches of the tributaries of the Rio Paraná. Additionally a dichotomic identification key of the M. pictus species group is provided.
Keywords: Cerrado; Conservation; Diversity; Killifish; Taxonomy